PENGARUH KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN SUB SEKTOR TRANSPORTASI DENGAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY SEBAGAI VARIABEL PEMODERASI TAHUN 2011-2016 - Amalia, Amara; Gunistiyo, Mr.; Utami, Yuni (PERMANA, 2017)
The Influence of Financial Performance on Corporate Value of Sub Sector of Transportation With Disclosure of Corporate Social Responsibility as Moderator of Year 2011-2016. He purpose of this research is 1) to analyze the influence of financial performance to company value, 2) to analyze the influence of financial performance to corporate value which moderated by corporate social responsibility. Hypothesis in this research is 1) there is influence of financial performance to company value, 2) corporate social responsibility able to moderate influence of financial performance to company value. In this research used quantitative research type with descriptive approach. Data collection method used in this research is documentation method. Data analysis techniques used are classical assumption testing, simple regression analysis and moderated regression analysis (MRA). From the results of simple regression sigifikansi test, the results of this study indicate that the financial performance variables significantly influence the value of transportation service sub-sector companies listed on the Indonesia Stock Exchange 2011-2016 at the level of 5%, evidenced from the simple regression significance of 0.000 <0, 05. From the result of the test of sigifikansi moderated regression analysis (MRA), the result of this research indicates that corporate social responsibility is not able to moderate the influence of financial performance to the value of transportation service sub-sector listed in Indonesia Stock Exchange 2011-2016 at level 5% of the significance value of moderated regression analysis of 0.356> 0.05. From the analysis results can be seen the value of coefficient of determination of 0.301 which means the variability of corporate value that can be explained by the financial performance is 30.1%. This means that 30.1% of corporate value is influenced by financial performance variable while the rest 69.9% by other factors that can not be explained.  Keywords: financial performance, corporate value, corporate social responsibility